KAJIAN KARAKTERISTIK PENCAHAYAAN BUATAN PADA BIOSKOP (STUDI KASUS : CINEMACITRA XXI,MALL CIPUTRA,KOTA SEMARANG) - Khamairah, Nadiah; Wahyuningrum, Sri Hartuti (architecture department, Engineering faculty, Universitas Diponegoro, 2017)
Architecture is a science that covers many areas of other scientific aspects. One aspect considered in architectural design is building utilities. Building utilities are the completeness of building facilities aimed at achieving the elements of comfort, health, safety, ease of communication and mobility in the building so that sustainability activity in the building can run with the best. One of the main aspects of building utilities is lighting. Lighting is divided into natural lighting and artificial lighting.Â Artificial Lighting is the lighting produced by a light source other thanÂ natural light. Artificial lighting is necessary if the position of the room is difficult to achieve by natural lighting or when natural lighting is insufficient. This paper will be studied artificial lighting characteristic in cinema Citra XXI Semarang.is a space in certain locations which being owned by some societies and being use together with other societies in needs.